A novel quasi-type-1 PLL based on frequency-fixed complex filter for three phase grid synchronization - Yunlu Li (Elsevier, 2022)
In practical applications of distributed generation, accurate phase and frequency detection of grid voltages is the critical aspect for the control of power converter. Thanks for its similarity and robustness, phase-locked loop (PLL) has been widespread. However, under distorted grid conditions with polluted harmonics, the accuracy of phase detection may be deteriorated. It is still a challenge to maintain the accuracy of phase detection and dynamic performance at same time. In this paper, to tackle this issue, a novel quasi-type-1 (QT1) structure based PLL is proposed. QT1-PLL incorporated with complex filter can meet the requirement of filtering capability, dynamic response and robustness. The utilization of complex filter based on frequency-fixed structure and feed-forward phase compensation path can eliminate the phase error oriented from frequency deviation. The results of comparative experiments confirm the effectiveness of the proposed PLL.